Compressive strength of corn kernels subjected to drying under different rest periods - Acácio Mabasso, Geraldo; Cambuy Siqueira, Valdiney; Darci Quequeto, Wellytton; Resende, Osvaldo; Duarte Goneli, André Luís (Revista Ciência Agronômica, 2020)
Mechanical properties of agricultural products are essential for a proper project design or processing equipment dimensioning, as well as for establishment of parameters on the supported load. An experiment was set up in a completely randomized design, with five treatments (continuous and intermittent drying under 4, 8, 12, and 16 h of rest period) and four replications, to evaluate the effect of intermittent drying. Corn kernels of the cultivar Cargo TL were harvested with a moisture content of 25.37% wb and submitted to drying in an experimental fixed bed dryer set to a temperature of 100 °C and an airflow of 1.5 m3 min-1 m-2. Drying was performed until the kernels reached a moisture content of 14±0.3% wb. The process was interrupted in the intermittent drying with a moisture content of 18±0.2% wb and continued after rest period until the final moisture content was reached. The analysis consisted of 10 kernels randomly selected per replication and submitted to the uniaxial compression test after determining their dimensions. Rupture force, maximum deformation, energy to rupture point, modulus of toughness, hardness, and drying rate during drying were evaluated. The increase in rest period promoted a linear increase in the rupture force and hardness. Modulus of toughness, energy to rupture point, and maximum deformation were not affected by the rest period. The increase in rest period contributed to increasing the drying rate.